Mesh repair versus mayo repair for paraumbilical hernia: a comparative study - Naik C., Shashidhara; K., Seshagiri Rao; D. M., Abhinava; Manangi, Mallikarjuna N.; C. S., Santhosh; Nagaraj, Niranjan (International Surgery Journal, 2018)
Background: Para umbilical hernia is a multifactorial and complex process they are most commonly found along the midline linea Alba. This study aims to assess the efficacy of mesh repair in comparison to Mayo Repair and to analyze the morbidity associated with the management. Methods: The study was conducted in Victoria Hospital and Bowring and Lady Curzon Hospital attached to Bangalore Medical College & Research Institute, with clinical features suggestive of Paraumbilical Hernia (Minimum 30 cases each) from October 2010 to September 2012. Pediatric age group and those patients requiring emergency surgery have been excluded. 30 patients underwent Mayo’s repair and 30 patients underwent Mesh repair. Follow up period ranged from 2 months to 24 months. Results: paraumbilical hernia was found more commonly between 4rd and 6th decade of life with female: male 2.3:1. Most common presenting symptom was swelling with cough impulse (36.5%) and reducibility present. Commonest predisposing factors were multiparty and obesity. Percentage of early postoperative complications in Mayo’s repair was 13.6% and in Mesh repairs 6.6%. No statistical difference was noted. Percentage of recurrence following Mayo’s repair was 10% and following mesh repair was 0%. Postoperative complications like seroma, infections were similar in both procedures (Mayo’s repair and Mesh repair). Conclusions: Prosthetic mesh repair is a technique with good post-operative outcome, low recurrent rate and excellent patient satisfaction. It could become the gold standard in adult umbilical and paraumbilical hernia repair, in the future.